2005
DOI: 10.1158/1078-0432.ccr-05-0439
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Thrombospondin-1 in Resected Colorectal Liver Metastases Predicts Poor Prognosis

Abstract: Purpose: The aim of this study was to examine the expression and prognostic relevance of thrombospondin-1 (TSP-1) in tumor biopsies taken from a consecutive series of liver resections done at the University Hospitals of Leicester and the Royal Liverpool Hospital. Experimental Design: Patients having undergone a liver resection for colorectal liver metastases at our institutions between 1993 and 1999 inclusive were eligible. Inclusion criteria were curative intent, sufficient tumor biopsy, and patient follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
1
23
0
3
Order By: Relevance
“…It regulates the growth metastasis and angiogenesis in various tumors and is significant in predicting tumor malignancy. Some researches in their studies found that TSP-1 was distributed in the cytoplasm of tumor cells in thyroid cancer [31], breast cancer [32], hepatocellular carcinoma [33], gastric carcinoma [34], and CRC [19]; while others studies showed that TSP-1 was mainly expressed in the ECM in pancreatic cancer [35], CRC [16], esophageal squamous cell carcinoma [36], non-small cell lung cancer [10], ductal in situ carcinoma of the breast [37]. However, others studies reported TSP-1 expression in both cytoplasm and stroma, as well in CRC [9], bladder cancer [13], and breast cancer [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It regulates the growth metastasis and angiogenesis in various tumors and is significant in predicting tumor malignancy. Some researches in their studies found that TSP-1 was distributed in the cytoplasm of tumor cells in thyroid cancer [31], breast cancer [32], hepatocellular carcinoma [33], gastric carcinoma [34], and CRC [19]; while others studies showed that TSP-1 was mainly expressed in the ECM in pancreatic cancer [35], CRC [16], esophageal squamous cell carcinoma [36], non-small cell lung cancer [10], ductal in situ carcinoma of the breast [37]. However, others studies reported TSP-1 expression in both cytoplasm and stroma, as well in CRC [9], bladder cancer [13], and breast cancer [38].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with primary CRC with low TSP-1 expression with or without detection of mp53 gene product are more likely to harbor lymph node metastasis than patients with higher expression [41]. Sutton et al, reported that TSP-1 is expressed differently in liver metastasis when compared with the primary tumor, possibly showing different modes of action such as facilitating tumor invasion rather than acting as antiangiogenic growth factor [16]. Maeda et al, concluded in their work, that patients with TSP-1 negative tumors had a significantly worse prognosis than those with TSP-1 positive tumors and the frequency of hepatic recurrence was significantly higher in patients with tumors that were TSP-1 negative [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HBD has been involved in the disassembly of focal contacts and stimulation of endothelial cell migration (Murphy-Ullrich et al, 1993;Vogel et al, 1993). Importantly, a few recent clinical studies suggest that the anti-angiogenic capacity of TSP-1 was decreased in metastatic deposits, as compared with less advanced primary tumors (Sutton et al, 2005) and that its expression by tumor cells was associated with the presence of venous invasion and with VEGF expression (Poon et al, 2004). Moreover, it was shown that some human cancers can bypass the angioinhibitory effects of TSP-1, by an intricate mechanism, which seems to involve the local balance of VEGF and TSP-1-activated transforming growth factor-b (TGF-b) (Filleur et al, 2001;Fontana et al, 2005).…”
mentioning
confidence: 99%
“…To our knowledge, the prognostic significance of THBS-1 mRNA expression in breast cancer has never been confirmed (40,41). On the contrary, in other tumors several studies reported a favorable prognostic value of THBS-1 expression (42,43), while others suggested a negative impact on survival (44,45). Certain investigators have linked increased blood THBS-1 protein expression with an aggressive phenotype in breast (35) and colon cancer (46).…”
Section: Patients ---------------------------------------------------mentioning
confidence: 99%